Proinflammatory cytokines modify Ca2+ signaling and induce an apoptotic lipidome in murine small intestinal organoids - Pauer, Svenja Mareike; Schindler, Alina; Ghezellou, Parviz; Spengler, Bernhard; Diener, Martin; Ballout, Jasmin (Frontiers in Physiology, 2026)
BackgroundInflammatory bowel diseases (IBD) are associated with elevated levels of proinflammatory cytokines exerting a detrimental effect on the intestinal epithelium. Since contradictory studies regarding time-dependent actions on epithelial secretion exist, intestinal organoids were treated with a mix of proinflammatory cytokines.MethodsLong-term (1–5 days) effects of a cytokine mix consisting of tumor necrosis factor α, interleukin-1β and interferon-γ on murine small intestinal epithelial organoids were investigated using live cell imaging, immunofluorescent staining, qPCR, scanning microprobe matrix-assisted laser desorption/ionization mass spectrometry imaging (AP-SMALDI MSI), and liquid-chromatography tandem mass spectrometry (UHPLC MS/MS).ResultsTreatment with the cytokine mix resulted in an enlarged organoid lumen. Stimulation of Cl– secretion seems to underly this swelling since it was inhibited by bumetanide, a blocker of Na+-K+-2Cl– cotransporters. Ca2+ imaging experiments revealed that the cytokine mix time-dependently enhanced the response to carbachol, a Ca2+-dependent secretagogue, which would favor Ca2+-dependent Cl− secretion. This was concomitant with an upregulated gene expression of inositol-1,4,5-trisphosphate receptor type 1 (IP3R1) and stromal interaction molecule 2 (STIM2), which is involved in store-operated Ca2+ entry. The cytokines induced apoptosis in organoids confirmed by an increase in caspase 3-immunopositive cells. Lipidomic analysis using UHPLC MS/MS revealed an upregulation of ceramides, sphingomyelins and ether-linked lipids within the epithelial cells. AP-SMALDI MSI showed an accumulation of ceramide-positive (apoptotic) cells within the organoid lumen.ConclusionProinflammatory cytokines induce fluid secretion and transiently upregulate Ca2+ signaling concomitant with the induction of an apoptotic lipidome in small intestinal organoids.